Protective Effect of Algerian Genista vepres Pomel Plant Against Isoniazid and Rifampicin Induced Liver Injury in Wistar Albino Rats - Zehani, Lamia; Kerkatou, Wafa; Hamdouche, Souad; Lassed, Somia; Boumaza, Ouahiba; Benayache, Fadila; Benayache, Samir; Zama, Djamila (Current Bioactive Compounds, 2022)
Background: The aim of the present study is to evaluate the protective effect of n- BuOH fraction of Genista vepres Pomel and Vitamin E against Isoniazid and Rifampicin (INH- RIF)-induced liver injury. Methods: Male Wistar Albino rats were divided into eight equal groups treated with plant fraction (50 mg/kg, 100 mg/kg), vitamin E (100 mg/kg) and INH-RIF (100 mg/kg body weight /day each). At the end of the experiment, animals were dissected and samples (blood, liver tissue) were removed and isolated for biochemical and histological studies. Results: Administration of INH-RIF for 21 days resulted in hepatic failure as evidenced by the elevation of biochemical parameters levels and hepatic oxidative stress, which was associated with extensive hepatic parenchyma alteration. The pretreatment of the rat with G. vepres Pomel attenuated the increase of hepatic dysfunction markers, significantly decreased the level of malondialdehyde (MDA), and increased GSH level, GPx and catalase activities compared to INH-RIF treated group. However, the Vitamin E co-treatment decreased MDA level and increased GPx activity but did not show any effect on catalase or GSH parameters. The histopathological studies on the liver of rats also supported that both plant fraction and vitamin E markedly reduced the toxicity of INH-RIF and preserved the histoarchitecture of liver tissue. Conclusion: The results suggested that the n-BuOH fraction of G. vepres Pomel acts as a potent hepatoprotective agent against INH-RIF-induced Hepatic dysfunction in rats.
Keywords: rifampicin